Crop Residue Biomass Effects on Agricultural Runoff - Damodhara R. Mailapalli; Martin Burger; William R. Horwath; Wesley W. Wallender (Applied and Environmental Soil Science)
High residue loads associated with conservation tillage and cover cropping may impede water flow in furrow irrigation and thus decrease the efficiency of water delivery and runoff water quality. In this study, the biomass residue effects on infiltration, runoff, and export of total suspended solids (TSS), dissolved organic carbon (DOC), sediment-associated carbon (TSS-C), and other undesirable constituents such as phosphate (soluble P), nitrate (), and ammonium () in runoff water from a furrow-irrigated field were studied. Furrow irrigation experiments were conducted in 91 and 274 m long fields, in which the amount of residue in the furrows varied among four treatments. The biomass residue in the furrows increased infiltration, and this affected total load of DOC, TSS, and TSS-C. Net storage of DOC took place in the long but not in the short field because most of the applied water ran off in the short field. Increasing field length decreased TSS and TSS-C losses. Total load of , , and soluble P decreased with increasing distance from the inflow due to infiltration. The concentration and load of P increased with increasing residue biomass in furrows, but no particular trend was observed for and . Overall, the constituents in the runoff decreased with increasing surface cover and field length.